2022
DOI: 10.1109/access.2022.3186678
|View full text |Cite
|
Sign up to set email alerts
|

Portable All-in-One Electroanalytical Device for Point of Care

Abstract: Recent technological advancements such as an expansion of available biomarkers and an incremental burden of chronic and infectious diseases made point of care (POC) devices in strong demand. It has a potential to surpass conventional lab-based devices in terms of time, cost, accessibility, and even accuracy. This potential strongly depends on an availability of affordable and miniaturized electronic POC devices that can provide a fast and sensitive response. This paper presents an all-in-one electroanalytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Primary studies assessing cost effectiveness could potentially assist in evaluating generated data and developing future studies that assess the sustainability of REASSURED POC devices in SSA. Our study further revealed the vast contrast in the amount of knowledge generated through primary studies from lab-based REASSURED diagnostics compared to studies generated for POC tests which are user-friendly for patients [18,[20][21][22][23][24]29,37]. We could not retrieve any evidence on the SARS-CoV-2 virus REASSURED POC tests despite the scale of the pandemic.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Primary studies assessing cost effectiveness could potentially assist in evaluating generated data and developing future studies that assess the sustainability of REASSURED POC devices in SSA. Our study further revealed the vast contrast in the amount of knowledge generated through primary studies from lab-based REASSURED diagnostics compared to studies generated for POC tests which are user-friendly for patients [18,[20][21][22][23][24]29,37]. We could not retrieve any evidence on the SARS-CoV-2 virus REASSURED POC tests despite the scale of the pandemic.…”
Section: Discussionmentioning
confidence: 69%
“…Full-article screening led to the inclusion of five articles and exclusion of 19 articles which did not meet the inclusion criteria (Fig 1). Articles were excluded due to the following reasons: reported on laboratory-based POC diagnostic services [18][19][20][21][22][23][24][25][26][27], were not conducted in SSA [18,24,[26][27][28][29], commentary article [30], and focused on the wrong population [27,28].…”
Section: Screeningmentioning
confidence: 99%
“…The enzymes glucose oxidase (GOD) and horseradish peroxidase (HRP) are required to make a glucose solution. 32 Hence, a 12 mM glucose solution was prepared using a buffer solution and D-(+)-Glucose (⩾99.5%). All the chemicals were purchased at Sigma-Aldrich (MA, USA).…”
Section: Error Rate I I Imentioning
confidence: 99%
“…Figure 2 illustrates a block diagram of the firmware for the amperometry. 32 For establishing the amperometry circuit, internal blocks of the MCU are utilized like 8-bit digital to analog converter (DAC), operational amplifier (op-amp), TIA, and 12-bit analog to digital converter (ADC) as shown in Fig. 2.…”
Section: System Designmentioning
confidence: 99%
“…[237] Park et al proposed an all-in-one electroanalytical device (AED), a miniaturized electronic POC device integrated with the most used electroanalytical techniques, such as amperometric, voltammetric, potentiometric, conductometric, and impedimetric techniques. [238] In simultaneous sensing, less solution is needed for analysis, enabling the practical use of matrixes that may be difficult to harvest, such as sweat or breath. [239,240] The potential for sweat or breath to become the matrix of choice for roadside tests and wearable biosensors is increasing, as sensors can detect progressively smaller concentrations of biomarkers.…”
Section: Integrated Sensing Systems and Simultaneous Detection Of Bio...mentioning
confidence: 99%